Precise Molecular Design for Two Parent BN‐Pentacyclic Isomers Through Stitching Engineering Toward Extremely Sensitive Explosive Detection. Issue 3 (19th December 2022) - Huang, Huanan; Yao, Junxiong; Xu, Han; Li, Jiaqi; Wang, Hanbin; Xiong, Cheng; Fang, Binhua; Wang, Yawei; Zhou, Ying; Cao, Xiaohua; Wang, Jianguo; Tang, Ben Zhong
Abstract: The incorporation of BN units into polycyclic aromatic hydrocarbons (PAHs) has been ascertained to be a promising strategy for creating novel materials with unique functions and properties. However, it poses a formidable challenge to achieve precise construction of BN‐PAHs with variable skeleton module, which conversely, enhances greater understanding of the structure‐property relationship. Herein, two BN‐pentacyclic isomers (P‐BN‐BT and I‐BN‐BT) with different stitching patterns are addressed comprehensively, in which the integrated analysis reveals that the geometric structure, aromaticity, and photophysical properties indeed vary with the variational stitching models. More interestingly, further investigations show that the I‐BN‐BT with twisted molecular configuration displays a low fluorescence quantum yield, while the P‐BN‐BT with fully planar conformation exhibits high quantum yield and exceptional mechanochromic luminescent (MCL) properties. More importantly, P‐BN‐BT shows extreme sensitivity toward 2, 4, 6‐trinitrophenol (TNP). Visual detection of TNP is handily performed by fabrication of the test strips, which reaches ppm level under daylight. This work provides systematic insight into the effects of BN doping and highlights the importance of accurate control of the stitching patterns in conjugated materials. Abstract : Two BN‐pentacyclic isomers have been designed through stitching engineering. Integrated analysis reveals that the geometric structure, aromaticity, and photophysical properties vary with the disparate stitching modes. This work provides insight into the effects of BN doping and highlights the importance of accurate control of the BN substitution patterns in conjugated materials.